Cultivating the next generation of pasture scientists in Australia - Bennett, Sarita (New South Wales Department of Primary Industry, 2013)
Current students coming through agricultural faculties in Australian universities have grown up in an era of low wool and meat prices, the introduction and acceptance of no-till farming as the norm and a general decrease in mixed farming landscapes in favour of continuous cropping. Since the collapse of the wool reserve price scheme in 1991, wool prices declined and income on wool producing farms followed suit. R & D during this period has also declined from 5-4% agricultural GDP in 1986 to only 3% in 2005 and has favoured research related to cropping rather than that related to pastures and livestock. How then do we convince students that mixed-farming enterprises provide the sustainable future of farming? This paper provides a background to farming practises over the last 20 years, along with the economic, environmental and social basis for the decisions that have been made. In view of a changing climate, peak oil, food security issues and changing trends for global food consumption, it will then set the scene and discuss why pastures and livestock should be an integral component of future farming systems. Finally, it will discuss how we can change a whole generation of future farmers and researchers to see the value of livestock and pastures in their farming landscapes. Current price increases for wool and meat, and the value of spreading risk on-farm in an increasingly variable climate will provide a basis for this decision.